INO80 represses osmostress induced gene expression by resetting promoter proximal nucleosomes - Klopf, Eva (Nucleic Acids Res, 2017)
The conserved INO80 chromatin remodeling complex is involved in regulation of DNA damage repair, replication and transcription. It is commonly recruited to the transcription start region and contributes to the establishment of promoter-proximal nucleosomes. We find a substantial influence of INO80 on nucleosome dynamics and gene expression during stress induced transcription. Transcription induced by osmotic stress leads to genome-wide remodeling of promoter proximal nucleosomes. INO80 function is required for timely return of evicted nucleosomes to the 5΄ end of induced genes. Reduced INO80 function in Arp8-deficient cells leads to correlated prolonged transcription and nucleosome eviction. INO80 and the related complex SWR1 regulate incorporation of the H2A.Z isoform at promoter proximal nucleosomes. However, H2A.Z seems not to influence osmotic stress induced gene regulation. Furthermore, we show that high rates of transcription promote INO80 recruitment to promoter regions, suggesting a connection between active transcription and promoter proximal nucleosome remodeling. In addition, we find that absence of INO80 enhances bidirectional promoter activity at highly induced genes and expression of a number of stress induced transcripts. We suggest that INO80 has a direct repressive role via promoter proximal nucleosome remodeling to limit high levels of transcription in yeast.